Neuroanesthesia Management of Complex Meningioma Case: A Comprehensive Approach for Minimizing Edema and Bleeding - Krisnayanti, Ida Ayu Arie; Suarjaya, I Putu Pramana; Juwita, Nova; Adhi Putra, Hendrikus Gede Surya (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2024)
Introduction: Meningioma is an extra-axial tumor originating from the arachnoid membrane cells. Most meningiomas are benign, circumscribed, slow growing and can be treated surgically according to the location of the lesion. The three main symptoms are headache, altered mental status and paralysis. Case Illustration: This case report discusses about A 41-year-old female patient came in conscious condition complaining of head pain that had been complaining since 2 years ago accompanied by complaints of nausea, vomiting and tonic-clonic seizures which were complained of 1 day before surgery. MRI examination of the brain with contrast, suggest a solid mass stinging firm contrast, dural tail is present, accompanied by perifocal edema measuring 4 x 4.1 x 4 cm in the right sphenoid wing urging the brainstem and midline to the left as far as 0.6 cm, depressing the optic chiasma and extending to the cavernous sinus tract right optic view shows a meningioma. The patient was managed under general anesthesia and lumbar drainage to reduce perioperative intracranial pressure. Conclusion: Various neuroanesthesia approaches including patient positioning, optimal neuroanesthesia management are needed so that oedema and bleeding from surgery can be minimized.